Differential dynamics and impacts of prophages and plasmids on the pangenome and virulence factor repertoires of Shiga toxin-producing Escherichia coli O145:H28. Issue 1 (14th January 2020) - Nakamura, Keiji; Murase, Kazunori; Sato, Mitsuhiko P.; Toyoda, Atsushi; Itoh, Takehiko; Mainil, Jacques Georges; Piérard, Denis; Yoshino, Shuji; Kimata, Keiko; Isobe, Junko; Seto, Kazuko; Etoh, Yoshiki; et al.
Abstract : Phages and plasmids play important roles in bacterial evolution and diversification. Although many draft genomes have been generated, phage and plasmid genomes are usually fragmented, limiting our understanding of their dynamics. Here, we performed a systematic analysis of 239 draft genomes and 7 complete genomes of Shiga toxin (Stx)-producing Escherichia coli O145:H28, the major virulence factors of which are encoded by prophages (PPs) or plasmids. The results indicated that PPs are more stably maintained than plasmids. A set of ancestrally acquired PPs was well conserved, while various PPs, including Stx phages, were acquired by multiple sublineages. In contrast, gains and losses of a wide range of plasmids have frequently occurred across the O145:H28 lineage, and only the virulence plasmid was well conserved. The different dynamics of PPs and plasmids have differentially impacted the pangenome of O145:H28, with high proportions of PP- and plasmid-associated genes in the variably present and rare gene fractions, respectively. The dynamics of PPs and plasmids have also strongly impacted virulence gene repertoires, such as the highly variable distribution of stx genes and the high conservation of a set of type III secretion effectors, which probably represents the core effectors of O145:H28 and the genes on the virulence plasmid in the entire O145:H28 population. These results provide detailed insights into the dynamics of PPs and plasmids, and show the application of genomic analyses using a large set of draft genomes and appropriately selected complete genomes.